Finding a story for ending mental health stigma - Fleming, Kevin Casey, author; Champ, Joseph, advisor; Long, Marilee, committee member; Kreston, Rosemary, committee member (Colorado State University. Libraries, 2015)
There is a discursive collision between the individual and the social models of disability, and mental health is at its focal point. Understanding this collision might help scholars and communication practitioners to better address one of the most troublesome public health issues— mental health stigma. There are multitudes of issues that exist at the heart of this discursive collision, and many are closely connected to mental health stigma. This thesis examines the issue of mental health stigma in a communications context. The study uses a qualitative focus group method to help elucidate how both mental health practitioners and non-professionals with expressed interests in reducing mental health stigma form their discourses about mental health conditions, the media, and society. The study seeks to identify practical narrative tools that communications practitioners could use for helping to de-marginalize people with mental health conditions. The study concludes with a call for communications practitioners to think more critically and creatively about how to approach reducing mental health stigma. Recommendations for practice and for future research are offered.